PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI - Rita Nengsih (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2021)
This study aims to examine the effect of financial performance and firm size simultaneously and partially on firm value in agricultural sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. Sampling was done by purposive sampling method which obtained 9 companies that met the specified sample criteria. Data were analyzed using multiple linear regression. The results show that financial performance and company size simultaneously and partially have a significant effect on firm value in agricultural sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. the correlation coefficient (R) of 0.461 indicates the degree of relationship between the independent variable and the dependent variable is 0.461 or 46.1%. While the coefficient of determination (R Square) of 0.368 means that the ability of the independent variables (financial performance and firm size) in explaining the dependent variable (firm value) is 0.368 or 36.8% and the remaining 63.2% is explained by other variables outside this research.